Construction of two enhanced plant flower-specific bidirectional promoters through overlap extension PCR - ZHANG Xiongfei; LIU Yali; LOU Qian; QI Yinyan; DU Lingjuan (浙江大学学报. 农业与生命科学版, 2013)
Promoter is a key element on gene expression regulation, and it is an emphasis of plant transgenic research. Now, detailed analysis about flower-specific promoters such as chalcone synthase gene promoter from petunia and lily has been made. Enhancer is another kind of regulatory element usually placed at upstream of promoter sequence. In order to precisely regulate gene expression in plant genetic engineering, scientists put forward a method of designing artificial promoter to avoid homology-dependent gene silencing caused by repeatedly using a same promoter sequence. In addition, in order to decrease the size of foreign gene and conform to the trend of multiple genes transformation, the method of using bidirectional promoter was proposed by scientists. According to the previous studies, the present study use core sequence of petunia flower-specific promoter pPCHS and lily flower-specific promoter pLCHS, CaMV 35S enhance sequence, OCS enhance sequence to design and construct two enhanced plant flower-specific bidirectional promoters. We wish to provide some promoters with practical value when we try to use multiple genes transformation method to precisely regulate ornamental traits of some important flower species such as petunia and lily.In this research, according to the procedure of overlap extension PCR method and sequences of petunia flower-specific promoter pPCHS, lily flower-specific promoter pLCHS, CaMV 35S enhancer, OCS enhancer, 10 primers were designed and synthesized firstly. In the first round of PCR process, plasmids which contain above-mentioned four sequences were templates; six fragments with overlapping areas were amplified using overlapping primers. These six fragments were named as pPCHS-1-2, pPCHS-1-3, 35S-4-5, OCS-6-7, pLCHS-8-10, pLCHS-9-10. Moreover, Prime Star™ HS DNA Polymerase was used in this PCR process and these six products were all bluntended. In the second round of PCR process, the mixture of products pPCHS-1-2, 35S-4-5, pLCHS-8-10 was a group of template, the mixture of products pPCHS-1-3, OCS-6-7, pLCHS-9-10 was another group, the upstream primer of pPCHS sequence and downstream primer of pLCHS sequence formed a pair of primers. Two products fused with various 3 fragments were produced after overlap extension in this PCR process. Ordinary DNA amplification enzyme was used in the second PCR process; products were cloned through TA clone method and then transferred into E. coli TOP10 for sequencing and preservation.After final sequencing, two fragments pPCHS-35S enhancer-pLCHS and pPCHS-OCS enhancer-pLCHS obtained via overlap extension PCR method were of the same length as our designed two bidirectional promoters, mutation or mismatch did not happen in their sequences, especially some important cis-acting elements. So we successfully acquired two enhanced plant flower-specific bidirectional promoters.In our opinion, selection of promoter with practical value is a basic work in transgenic research, how to design and construct artificial promoters maybe a considerable area and the study of artificial bidirectional promoters are a new area in the research of promoter. Two enhanced plant flower-specific bidirectional promoters were rapidly and simply constructed through overlap extension PCR method in this work, we hope they become available molecular tools in ornamental plant genetic engineering.